Dam-induced disruption of hydrochory and macrophyte recovery in the Brisbane River post-flood - Colin L. Burke; Luke Carpenter-Bundhoo; David T. Roberts; Hannah M. Franklin; Mark J. Kennard (Aquatic Botany, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Guidance on selecting and evaluating AI auto-segmentation systems in clinical radiotherapy: insights from a six-vendor analysis - Branimir Rusanov; Martin A. Ebert; Mahsheed Sabet; Pejman Rowshanfarzad; Nathaniel Barry; Jake Kendrick; Zaid Alkhatib; Suki Gill; Joshua Dass; Nicholas Bucknell; Jeremy Croker; Colin Tang; et al. (Physical and Engineering Sciences in Medicine, 2025)
Artificial Intelligence (AI) based auto-segmentation has demonstrated numerous benefits to clinical radiotherapy workflows. However, the rapidly changing regulatory, research, and market environment presents challenges around selecting and evaluating the most suitable solution. To support the clinical adoption of AI auto-segmentation systems, Selection Criteria recommendations were developed to enable a holistic evaluation of vendors, considering not only raw performance but associated risks uniquely related to the clinical deployment of AI. In-house experience and key bodies of work on ethics, standards, and best practices for AI in Radiation Oncology were reviewed to inform selection criteria and evaluation strategies. A retrospective analysis using the criteria was performed across six vendors, including a quantitative assessment using five metrics (Dice, Hausdorff Distance, Average Surface Distance, Surface Dice, Added Path Length) across 20 head and neck, 20 thoracic, and 19 male pelvis patients for AI models as of March 2023. A total of 47 selection criteria were identified across seven categories. A retrospective analysis showed that overall no vendor performed exceedingly well, with systematically poor performance in Data Security & Responsibility, Vendor Support Tools, and Transparency & Ethics. In terms of raw performance, vendors varied widely from excellent to poor. As new regulations come into force and the scope of AI auto-segmentation systems adapt to clinical needs, continued interest in ensuring safe, fair, and transparent AI will persist. The selection and evaluation framework provided herein aims to promote user confidence by exploring the breadth of clinically relevant factors to support informed decision-making.

Charting water quality improvements and practice reversion with pesticide interventions at catchment scale - Luke Farrow; Catherine Glass; Phoebe Alice Morton; W. Colin McRoberts; Stewart Floyd; Diane Burgess; Philip Jordan; Rachel Cassidy (Science of The Total Environment, 2025)

Grazing impacts on experimentally restored aquatic macrophytes as critical habitat for the threatened Australian lungfish - Colin L. Burke; Luke Carpenter-Bundhoo; David T. Roberts; César Herrera; Hannah M. Franklin; Mark J. Kennard (Journal of Environmental Management, 2024)

Pathways from research to sustainable development: Insights from ten research projects in sustainability and resilience - Anna Scaini; Joseph Mulligan; Håkan Berg; Albert Brangarí; Vera Bukachi; Sebastian Carenzo; Da Chau Thi; Colin Courtney-Mustaphi; Anneli Ekblom; Hanne Fjelde; Mathias Fridahl; Anders Hansson; et al. (Ambio, 2024)
Drawing on collective experience from ten collaborative research projects focused on the Global South, we identify three major challenges that impede the translation of research on sustainability and resilience into better-informed choices by individuals and policy-makers that in turn can support transformation to a sustainable future. The three challenges comprise: (i) converting knowledge produced during research projects into successful knowledge application; (ii) scaling up knowledge in time when research projects are short-term and potential impacts are long-term; and (iii) scaling up knowledge across space, from local research sites to larger-scale or even global impact. Some potential pathways for funding agencies to overcome these challenges include providing targeted prolonged funding for dissemination and outreach, and facilitating collaboration and coordination across different sites, research teams, and partner organizations. By systematically documenting these challenges, we hope to pave the way for further innovations in the research cycle.

Mechanisms underpinning community stability along a latitudinal gradient: Insights from a niche‐based approach - Luke Christopher Evans; Yolanda Melero; Reto Schmucki; Philipp H. Boersch‐Supan; Lluís Brotons; Colin Fontaine; Frédéric Jiguet; Mikko Kuussaari; Dario Massimino; Robert A. Robinson; David B. Roy; Oliver Schweiger; et al. (Global Change Biology, 2023)
At large scales, the mechanisms underpinning stability in natural communities may vary in importance due to changes in species composition, mean abundance, and species richness. Here we link species characteristics (niche positions) and community characteristics (richness and abundance) to evaluate the importance of stability mechanisms in 156 butterfly communities monitored across three European countries and spanning five bioclimatic regions. We construct niche‐based hierarchical structural Bayesian models to explain first differences in abundance, population stability, and species richness between the countries, and then explore how these factors impact community stability both directly and indirectly (via synchrony and population stability). Species richness was partially explained by the position of a site relative to the niches of the species pool, and species near the centre of their niche had higher average population stability. The differences in mean abundance, population stability, and species richness then influenced how much variation in community stability they explained across the countries. We found, using variance partitioning, that community stability in Finnish communities was most influenced by community abundance, whereas this aspect was unimportant in Spain with species synchrony explaining most variation; the UK was somewhat intermediate with both factors explaining variation. Across all countries, the diversity–stability relationship was indirect with species richness reducing synchrony which increased community stability, with no direct effects of species richness. Our results suggest that in natural communities, biogeographical variation observed in key drivers of stability, such as population abundance and species richness, leads to community stability being limited by different factors and that this can partially be explained due to the niche characteristics of the European butterfly assemblage.

Bioclimatic context of species' populations determines community stability - Luke Christopher Evans; Yolanda Melero; Reto Schmucki; Philipp H. Boersch‐Supan; Lluís Brotons; Colin Fontaine; Frédéric Jiguet; Mikko Kuussaari; Dario Massimino; Robert A. Robinson; David B. Roy; Oliver Schweiger; et al. (Global Ecology and Biogeography, 2022)
Aim It is important to understand the factors affecting community stability because ecosystem function is increasingly at risk from biodiversity loss. Here, we evaluate how a key factor, the position of local environmental conditions within the thermal range of the species, influences the stability of butterfly communities at a continental scale. Location Spain, UK and Finland. Time period 1999–2017. Major taxa studied Butterflies. Methods We tested the following hypotheses about how species responses to temperature anomalies aggregate to influence stability: Hypothesis 1, species have contrasting responses to local temperature anomalies at opposing edges of their thermal range; hypothesis 2, communities with central thermal range positions have higher community stability; and the impacts of thermal range position on community stability are driven by hypothesis 3, population asynchrony, or hypothesis 4, additive population stability. Data were analysed at 876 sites for 157 species. Results We found some support for hypothesis 1, because there were interactions between thermal range and response to temperature anomalies such that species at different range edges could provide weak compensatory dynamics. However, responses were nonlinear, suggesting strong declines with extreme anomalies, particularly at the hot range edge. Hypothesis 2 was supported in part, because community stability increased with central thermal range positions and declined at the edges, after accounting for species richness and community abundance. Thermal range position was weakly correlated with asynchrony (hypothesis 3) and population stability (hypothesis 4), although species richness and population abundance had larger impacts. Main conclusions Future extreme heat events will be likely to impact species negatively across their thermal range, but might be particularly impactful on populations at the hottest end of the thermal range. Thermal range position influenced community stability because range edge communities were stable. However, the prediction of community stability from thermal range position is challenging because of nonlinear responses to temperature, with small temperature anomalies producing weak compensatory dynamics, but large extreme events synchronizing dynamics.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Oviposition behaviour and emergence through time of the small blue butterfly (Cupido minimus) in a nature reserve in Bedfordshire, UK - Esme Ashe-Jepson; Andrew J. Bladon; Greg Herbert; Gwen E. Hitchcock; Richard Knock; Colin B. H. Lucas; Sarah H. Luke; Edgar C. Turner (Journal of Insect Conservation, 2022)
Abstract Climate change affects butterflies in many ways, influencing the timing of emergence and reproduction, habitat preferences, and behaviour. The small blue ( Cupido minimus Fuessley, 1775) is highly specialised in its host plant requirements, feeding on the seeds of a single species, kidney vetch ( Anthyllis vulneraria ), on which the larvae occur singly to avoid cannibalism. The butterfly is likely to be vulnerable to temperature-related changes in oviposition, adult emergence, and host plant flowering times, and is, therefore, a good model species for investigating climate change-related impacts. Using 26 years of data from the national UK Butterfly Monitoring Scheme (1993–2019) from one nature reserve, and 4 years of targeted egg searches (2006, 2007, 2008, 2020) from three reserves in Bedfordshire, UK, we investigated the effects of local temperature on small blue emergence date and total abundance, whether flowerhead or local environmental characteristics predicted small blue oviposition behaviour, and whether this changed between years. Small blue adults emerged on earlier dates over time, and earlier in years with higher maximum February temperatures. Total adult abundance was not predicted by monthly temperatures or total abundance in the previous year. Oviposition behaviour was broadly consistent across years, with egg presence more likely and egg abundance higher on kidney vetch flowerheads that were taller than the surrounding vegetation, and surrounded by taller vegetation and fewer mature flowerheads. The effect of solar radiation differed between years, with a negative effect on the probability of egg presence in 2007 and 2008, but a positive effect in 2020. Egg abundance per flowerhead was highly variable between years, with 2006 having four times more eggs per flowerhead than other years. This was likely driven by high adult abundance in 2006, which could have increased competition for flowerheads. Implications for insect conservation Our results indicate that management for greater availability of taller kidney vetch amongst taller vegetation would encourage small blue oviposition on a greater number of flowerheads, providing a possible means of reducing competition and increasing larval survival, and that this would be effective despite variation in adult abundance between years. The high level of competition we observed in the year with the highest adult abundance indicates that higher numbers of host plants should be encouraged to reduce competition and larval cannibalism in peak years, increasing the likelihood of long-term population persistence and growth.

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Low dispersal and ploidy differences in a grass maintain photosynthetic diversity despite gene flow and habitat overlap - Jill K. Olofsson; Emma V. Curran; Florence Nyirenda; Matheus E. Bianconi; Luke T. Dunning; Vanja Milenkovic; Graciela Sotelo; Oriane Hidalgo; Robyn F. Powell; Marjorie R. Lundgren; Ilia J. Leitch; Patrik Nosil; et al. (Molecular Ecology, 2021)
Geographical isolation facilitates the emergence of distinct phenotypes within a single species, but reproductive barriers or selection are needed to maintain the polymorphism after secondary contact. Here, we explore the processes that maintain intraspecific variation of C 4 photosynthesis, a complex trait that results from the combined action of multiple genes. The grass Alloteropsis semialata includes C 4 and non‐C 4 populations, which have coexisted as a polyploid series for more than 1 million years in the miombo woodlands of Africa. Using population genomics, we show that there is genome‐wide divergence for the photosynthetic types, but the current geographical distribution does not reflect a simple habitat displacement scenario as the genetic clusters overlap, being occasionally mixed within a given habitat. Despite evidence of recurrent introgression between non‐C 4 and C 4 groups, in both diploids and polyploids, the distinct genetic lineages retain their identity, potentially because of selection against hybrids. Coupled with strong isolation by distance within each genetic group, this selection created a geographical mosaic of photosynthetic types. Diploid C 4 and non‐C 4 types never grew together, and the C 4 type from mixed populations constantly belonged to the hexaploid lineage. By limiting reproductive interactions between photosynthetic types, the ploidy difference probably allows their co‐occurrence, reinforcing the functional diversity within this species. Together, these factors enabled the persistence of divergent physiological traits of ecological importance within a single species despite gene flow and habitat overlap.

Incorporating connectivity into conservation planning for the optimal representation of multiple species and ecosystem services - Sara H. Williams; Sarah A. Scriven; David F. R. P. Burslem; Jane K. Hill; Glen Reynolds; Agnes L. Agama; Frederick Kugan; Colin R. Maycock; Eyen Khoo; Alexander Y. L. Hastie; John B. Sugau; Reuben Nilus; et al. (Conservation Biology, 2020)
Conservation planning tends to focus on protecting species’ ranges or landscape connectivity but seldom both—particularly in the case of diverse taxonomic assemblages and multiple planning goals. Therefore, information on potential trade‐offs between maintaining landscape connectivity and achieving other conservation objectives is lacking. We developed an optimization approach to prioritize the maximal protection of species’ ranges, ecosystem types, and forest carbon stocks, while also including habitat connectivity for range‐shifting species and dispersal corridors to link protected area. We applied our approach to Sabah, Malaysia, where the state government mandated an increase in protected‐area coverage of approximately 305,000 ha but did not specify where new protected areas should be. Compared with a conservation planning approach that did not incorporate the 2 connectivity features, our approach increased the protection of dispersal corridors and elevational connectivity by 13% and 21%, respectively. Coverage of vertebrate and plant species’ ranges and forest types were the same whether connectivity was included or excluded. Our approach protected 2% less forest carbon and 3% less butterfly range than when connectivity features were not included. Hence, the inclusion of connectivity into conservation planning can generate large increases in the protection of landscape connectivity with minimal loss of representation of other conservation targets.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Real-Time Monitoring with a Tablet App Improves Implementation of Treatments to Enhance Forest Structural Diversity - Colin T Maher; Emily Oja; Abigail Marshall; Matthew Cunningham; Lucas Townsend; Graham Worley-Hood; Luke Ruffner Robinson; Taylor Margot; Drew Lyons; Stuart Fety; Eryn E Schneider; Sean M A Jeronimo; et al. (Journal of Forestry, 2019)

C 4 anatomy can evolve via a single developmental change - Marjorie R. Lundgren; Luke T. Dunning; Jill K. Olofsson; Jose J. Moreno‐Villena; Jacques W. Bouvier; Tammy L. Sage; Roxana Khoshravesh; Stefanie Sultmanis; Matt Stata; Brad S. Ripley; Maria S. Vorontsova; Guillaume Besnard; et al. (Ecology Letters, 2019)
C 4 photosynthesis is a complex trait that boosts productivity in warm environments. Paradoxically, it evolved independently in numerous plant lineages, despite requiring specialised leaf anatomy. The anatomical modifications underlying C 4 evolution have previously been evaluated through interspecific comparisons, which capture numerous changes besides those needed for C 4 functionality. Here, we quantify the anatomical changes accompanying the transition between non‐C 4 and C 4 phenotypes by sampling widely across the continuum of leaf anatomical traits in the grass Alloteropsis semialata . Within this species, the only trait that is shared among and specific to C 4 individuals is an increase in vein density, driven specifically by minor vein development that yields multiple secondary effects facilitating C 4 function. For species with the necessary anatomical preconditions, developmental proliferation of veins can therefore be sufficient to produce a functional C 4 leaf anatomy, creating an evolutionary entry point to complex C 4 syndromes that can become more specialised.

Genome biogeography reveals the intraspecific spread of adaptive mutations for a complex trait - Jill K. Olofsson; Matheus Bianconi; Guillaume Besnard; Luke T. Dunning; Marjorie R. Lundgren; Helene Holota; Maria S. Vorontsova; Oriane Hidalgo; Ilia J. Leitch; Patrik Nosil; Colin P. Osborne; Pascal‐Antoine Christin (Molecular Ecology, 2016)
Physiological novelties are often studied at macro‐evolutionary scales such that their micro‐evolutionary origins remain poorly understood. Here, we test the hypothesis that key components of a complex trait can evolve in isolation and later be combined by gene flow. We use C 4 photosynthesis as a study system, a derived physiology that increases plant productivity in warm, dry conditions. The grass Alloteropsis semialata includes C 4 and non‐C 4 genotypes, with some populations using laterally acquired C 4 ‐adaptive loci, providing an outstanding system to track the spread of novel adaptive mutations. Using genome data from C 4 and non‐C 4 A. semialata individuals spanning the species’ range, we infer and date past migrations of different parts of the genome. Our results show that photosynthetic types initially diverged in isolated populations, where key C 4 components were acquired. However, rare but recurrent subsequent gene flow allowed the spread of adaptive loci across genetic pools. Indeed, laterally acquired genes for key C 4 functions were rapidly passed between populations with otherwise distinct genomic backgrounds. Thus, our intraspecific study of C 4 ‐related genomic variation indicates that components of adaptive traits can evolve separately and later be combined through secondary gene flow, leading to the assembly and optimization of evolutionary innovations.

The piggybacking stingray - Mark G. Meekan; Luke Trevitt; Colin A. Simpfendorfer; William White (Coral Reefs, 2016)

Antibiotic Resistance Among Cultured Bacterial Isolates from Bioethanol Fermentation Facilities Across the United States - Colin A. Murphree; E. Patrick Heist; Luke A. Moe (Current Microbiology, 2014)

Making decisions to conserve species under climate change - Luke P. Shoo; Ary A. Hoffmann; Stephen Garnett; Robert L. Pressey; Yvette M. Williams; Martin Taylor; Lorena Falconi; Colin J. Yates; John K. Scott; Diogo Alagador; Stephen E. Williams (Climatic Change, 2013)

Expression of biomineralization‐related ion transport genes in Emiliania huxleyi - Luke Mackinder; Glen Wheeler; Declan Schroeder; Peter von Dassow; Ulf Riebesell; Colin Brownlee (Environmental Microbiology, 2011)
Summary Biomineralization in the marine phytoplankton Emiliania huxleyi is a stringently controlled intracellular process. The molecular basis of coccolith production is still relatively unknown although its importance in global biogeochemical cycles and varying sensitivity to increased pCO 2 levels has been well documented. This study looks into the role of several candidate Ca 2+ , H + and inorganic carbon transport genes in E. huxleyi , using quantitative reverse transcriptase PCR. Differential gene expression analysis was investigated in two isogenic pairs of calcifying and non‐calcifying strains of E. huxleyi and cultures grown at various Ca 2+ concentrations to alter calcite production. We show that calcification correlated to the consistent upregulation of a putative HCO 3 ‐ transporter belonging to the solute carrier 4 (SLC4) family, a Ca 2+ /H + exchanger belonging to the CAX family of exchangers and a vacuolar H + ‐ATPase. We also show that the coccolith‐associated protein, GPA is downregulated in calcifying cells. The data provide strong evidence that these genes play key roles in E. huxleyi biomineralization. Based on the gene expression data and the current literature a working model for biomineralization‐related ion transport in coccolithophores is presented.

Epidemiology of neuroendocrine cancers in an Australian population - Colin Luke; Timothy Price; Amanda Townsend; Christos Karapetis; Dusan Kotasek; Nimit Singhal; Elizabeth Tracey; David Roder (Cancer Causes & Control, 2010)

Ecological assessment to detect imminent change in coral reefs of Admiral Cockburn Land and Sea National Park, Turks and Caicos Islands - Angela Dikou; Colin Ackerman; Carly Banks; Alex Dempsey; Michael Fox; Meagan Gins; Patricia Hester; Adam Parnes; Stephanie Roach; Jessica Rohde; Cliff Spital; Mackai Tapleshay; et al. (Marine Ecology, 2009)
Coral reefs of the Turks and Caicos Islands (TCIs) (Caribbean Sea) constitute some of the few pristine coral reef systems in the world and play a crucial role in the islands’ economy because they support rich fisheries catches and tourism development. Ambitious development plans involving increase in fishing and tourism pressures are about to bring changes in coastal zone resources of the TCIs associated with increased sediments and nutrients and reduced predation by herbivorous fish on coral reefs. Understanding change is critical when attempting to protect the resources that these coral reefs support and to adopt proper management strategies. Yet, an environmental assessment program to detect imminent human‐induced changes on the surrounding reefs of the TCIs is lacking. Thus, (i) we obtained baseline data on benthic composition and coral community structure at seven reef sites of representative reefs of the TCIs within the Admiral Cockburn Land and Sea National Park (ACLSNP) of South Caicos Island and (ii) performed a priori statistical power analysis to calculate replication requirements for safely and confidently detecting small (δ = 0.1), medium (δ = 0.3), and large (δ = 0.5) effect sizes for a number of relevant to anticipated changes, univariate, benthic indices and for power β = 0.95. The platforms of the margin reefs studied (9–12 m depth) appeared rather variable regarding benthic composition but quite homogeneous regarding hard coral community structure. Mean percent cover of algal functional groups was 0.1 ± 0.3 (mean ± sd) percent for coralline algae and Halimeda , 0.1 ± 0.6 (mean ± sd) percent for macroalgae, 21.7 ± 33 (mean ± sd) percent for turf algae and 4.8 ± 4.0 (mean ± sd) percent for hard coral cover. The dominant benthic component, however, was carbonate substrate (mean ± sd = 30.4 ± 34.3), thus indicating an accreting reef framework. Mean hard coral density, colony size and recruit density were 5.5 ± 1.8 (mean ± sd) corals per 20‐m line transect, 13.0 ± 2.3 (mean ± sd) cm maximum colony diameter, and 1.3 ± 1.4 (mean ± sd) recruits per square foot, respectively. Due to high natural variance, hard coral colony size and density were practically the most sensitive indices in detecting even small size changes on benthos. Also, the geometric mean of log‐transformed colony size‐frequency distributions of the most abundant hard coral taxa, i.e. Montastrea annularis , Agaricia spp., Siderastrea spp. and Porites asteroides were practically sensitive for the same purpose. We hope that the study will optimize the spatial component of a necessary environmental impact assessment program on coral reefs of the TCIs once the natural spatial variability of the system has been assessed and sensitive, benthic, univariate indices have been identified for representative reference coral reef sites of the TCIs.

Female philopatry in coastal basins and male dispersion across the North Atlantic in a highly mobile marine species, the sperm whale ( Physeter macrocephalus ) - DANIEL ENGELHAUPT; A. RUS HOELZEL; COLIN NICHOLSON; ALEXANDROS FRANTZIS; SARAH MESNICK; SHANE GERO; HAL WHITEHEAD; LUKE RENDELL; PATRICK MILLER; RENAUD DE STEFANIS; ANA CAÑADAS; SABINA AIROLDI; et al. (Molecular Ecology, 2009)
The mechanisms that determine population structure in highly mobile marine species are poorly understood, but useful towards understanding the evolution of diversity, and essential for effective conservation and management. In this study, we compare putative sperm whale populations located in the Gulf of Mexico, western North Atlantic, Mediterranean Sea and North Sea using mtDNA control region sequence data and 16 polymorphic microsatellite loci. The Gulf of Mexico, western North Atlantic and North Sea populations each possessed similar low levels of haplotype and nucleotide diversity at the mtDNA locus, while the Mediterranean Sea population showed no detectable mtDNA diversity. Mitochondrial DNA results showed significant differentiation between all populations, while microsatellites showed significant differentiation only for comparisons with the Mediterranean Sea, and at a much lower level than seen for mtDNA. Samples from either side of the North Atlantic in coastal waters showed no differentiation for mtDNA, while North Atlantic samples from just outside the Gulf of Mexico (the western North Atlantic sample) were highly differentiated from samples within the Gulf at this locus. Our analyses indicate a previously unknown fidelity of females to coastal basins either side of the North Atlantic, and suggest the movement of males among these populations for breeding.

Multiple primary cancers of separate organ sites: implications for research and cancer control (Australia) - Adrian Heard; David Roder; Colin Luke (Cancer Causes & Control, 2005)

A critical analysis of reasons for improved survival from invasive cutaneous melanoma - Colin Glen Luke; Brendon John Coventry; Erwin Joseph Foster-Smith; David Murray Roder (Cancer Causes & Control, 2003)